STEM-03. CONSUMPTION OF A HIGH-FAT DIET INHIBITS THE TUMOR SUPPRESSIVE ACTIVITY OF HYDROGEN SULFIDE, DRIVING CANCER STEM CELL ENRICHMENT AND DISEASE AGGRESSION IN GLIOBLASTOMA. (11th November 2019) - Silver, Daniel; Roversi, Gustavo; Bithi, Nazmin; Troike, Katie; Neumann, Chase; Mark Brown, J; Hine, Christopher; Lathia, Justin
Abstract: Glioblastoma (GBM) remains among the deadliest of human malignancies. Effective disease management is lacking due in part to the emergence of the cancer stem cell (CSC) phenotype. The tumor cell extrinsic, environmental, and lifestyle factors that result in CSC enrichment are not well understood. Alongside other pathological features, the CSC state endows populations of tumor cells with a fluid metabolic profile that enables utilization of multiple nutrition sources. Therefore, to test the impact of diet on CSC enrichment, we interrogated disease progression in tumor-bearing mice fed either a high-fat diet (HFD), similar to the Western Pattern diet or a control low-fat diet. Compared to controls, HFD-consumption resulted in the presentation of a hyper-aggressive disease phenotype with truncated survival and tumors markedly enriched in tumor-initiating SOX2 + CSCs. To understand the underlying mechanism driving this finding, we examined tumors for the diet-regulated metabolite hydrogen sulfide (H2 S). H2 S is an endogenously produced bio-active gasotransmitter similar to nitric oxide. It functions principally through protein S-sulfhydration to regulate a variety of cellular programs including mitochondrial function, stress signaling and metabolism. While there is exceedingly limited information on H2 S and GBM, its HFD-driven suppression has been reported in other organ systems. We discovered a significant reduction in H2 S synthesis resulting from HFD-consumption in the brain of the mouse and a striking decrease in protein S-sulfhydration in human GBM tumor tissue when compared to non-cancerous control brain tissue. We demonstrated that chemical inhibition of H2 S synthesis resulted in increased tumor cell viability whereas exposure to chemical H2 S donors led to pronounced cell death of cultured mouse and human GBM cells. These data demonstrate for the first time, that H2 S serves as a tumor suppressor for GBM. Moreover, the diet-driven suppression of H2 S helps explain the hyper-aggressive in vivo phenotype that presents in response to HFD-consumption.